Systematic Analysis of the Betula platyphylla TCP Gene Family and Its Expression Profile Identifies Potential Key Candidate Genes Involved in Abiotic Stress Responses - Shengzhou Guo; Yuan Xu; Yi Zhou; Ronglin Liu; Yongkang Wang; Ling Yao; Syed Muhammad Azam; Huanhuan Ma; Xiaomin Liu; Shijiang Cao; Kang Wang (Plants)
The TCP transcription factor (TF) family is a vital set of plant-specific regulators involved in plant growth, development, and responses to environmental stresses. Despite the extensive research on TCP transcription factors in numerous plant species, the functions they fulfill in Betula platyphylla are still not well understood. In this study, 21 BpTCP genes were identified via genome-wide analysis. Bioinformatics analysis was used to examine the physicochemical properties of these transcription factors, including molecular weight, isoelectric point, chromosomal distribution, and predicted subcellular localization. We expected that most BpTCP transcription factors would be located in the nucleus. Collinearity analysis revealed that gene fragment duplication events played a major role in the evolutionary expansion and diversification of the BpTCP gene family. Promoter analysis identified diverse cis-acting elements in BpTCP, suggesting that they play a role in stress responses, hormonal regulation, and plant growth and development. qRT-PCR analysis showed that BpTCP genes displayed tissue-specific expression patterns in the roots, stems, and leaves, displaying remarkable differences in expression levels when subjected to abiotic stresses, including drought and high- and low-temperature conditions. Notably, BpTCP17 and BpTCP18 showed markedly higher expression levels under multiple stress conditions. Subcellular localization experiments confirmed that both BpTCP17 and BpTCP18 localize in the nucleus, consistent with bioinformatic predictions. These findings emphasize the potential roles of BpTCP17 and BpTCP18 in mediating abiotic stress responses, highlighting their potential as candidate genes for improving stress tolerance in B. platyphylla.